Back Matter Jurnal Litbang Industri Vol. 8 No. 2 Desember Tahun 2018 - JLI Padang (Institution for Industrial Research and Standardization of Industry - Padang, 2018)
Back Matter Jurnal Litbang Industri Vol. 8 No. 2 Desember Tahun 2018